ROLECHECKER IN DISCOVERYTHE RISK OF MATERIAL MISSTATEMENT IN LIGHT OF THE APPLICATION OF THE INTERNATIONAL AUDITING STANDARD 240 - Nahla Mahmo o d Wah ee b; Asst. Prof.dr iman Shakir Mohammed (Scholar Express Journals, 2022)
This research is motivated by reform of regional finance, good governance, The research aims to identifyBezelThe auditor’s obligation to apply Auditing Standard 240 related to detecting fraud and identifying the risks of material misstatementWhen the financial statements, throughDesign a questionnaire in the form of a special questionknowinglyThe extent of the auditor's commitment to proceduresThe audit received in accordance with International Auditing Standard 240 when auditing financial statements, sohas been judgedresolutionFrom before(11)One of the auditing professors, and the notes were taken, modified, and then distributed to the research samplerepresented byFirst-class audit companies and offices that are in a general prospectus2022Issued by the Board of Auditing and Oversight Profession in IraqThe research reached the most important conclusions:There is no statistical significance for the external auditors in Iraq to follow the audit procedures contained in Standard No.(240)From the point of view of the sample members, this indicates that the external auditors in Iraq do not follow the audit procedures contained in Standard No.(240)When auditing the financial statementsThe research also reached the most important recommendations:The necessity for the Board of Audit and Oversight Profession in Iraq to educate and guide external auditors to follow audit procedures(Requirements)contained in International Auditing Standard No(240), because of its contribution to strengthening the auditors' reports, and obligating them to do so.
Keywords: Auditor; Material Misstatement; International Auditing Standard 240.